Prigionieri di guerra ungheresi all’Aquila (1915-1919) - Takács, Bálint (Italianistica Debreceniensis, 2018)
The aim of this paper is to present the life of Hungarian prisoners of war in the internment camps of L’Aquila, a city situated in the central part of Italy, during and after the Great War. The POWs were first detained in the caserma Castello (Castle barracks), which is a 16th-century fortress where units of the Italian Army were stationing as well at that time. This made it possible for the POWs to lead a relatively idyllic life, whose various aspects are examined in the paper, such as nutrition, accommodation, clothing, correspondence, religious life, daily routine and employment. The sources used include archival documents, two memoirs of ex-POWs and newspaper articles. The comfortable life of the POWs was dimmed by the lack of their families and the Homeland, the idleness and certain infectious diseases. From the summer of 1916, the prisoners were employed in agricultural and industrial works outside the prison camp and were hence transferred from the fortress to barracks and unused churches. It is unknown when the last Hungarian POW left L’Aquila, and yet one of them is proven to have been there still in July 1919.